2016
DOI: 10.1136/bmjopen-2016-012300
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the Mindful Student Study: a randomised controlled trial of the provision of a mindfulness intervention to support university students' well-being and resilience to stress

Abstract: IntroductionLevels of stress in UK university students are high, with an increase in the proportion of students seeking help in recent years. Academic pressure is reported as a major trigger. Mindfulness training has been shown to reduce stress and is popular among students, but its effectiveness in this context needs to be ascertained. In this pragmatic randomised controlled trial, we hypothesise that the provision of a preventative mindfulness intervention in universities could reduce students' psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 22 publications
1
48
0
3
Order By: Relevance
“…But, as a practice-based study, it differs from more recent ones which are larger dimensioned and more strictly organized on the current model of pragmatic trials. (57) This nonrandomized pragmatic study possesses the strengths and limitations (Tables 7 and 8) inherent in its nature of field study. Moreover, the two main arms being hands-on techniques in non-naïve population choosing their health care impacts heavily the design of the study (e.g., no randomized allocation, no blinding).…”
Section: The Clinical Effects Of the Different Conditions Is An Impormentioning
confidence: 99%
“…But, as a practice-based study, it differs from more recent ones which are larger dimensioned and more strictly organized on the current model of pragmatic trials. (57) This nonrandomized pragmatic study possesses the strengths and limitations (Tables 7 and 8) inherent in its nature of field study. Moreover, the two main arms being hands-on techniques in non-naïve population choosing their health care impacts heavily the design of the study (e.g., no randomized allocation, no blinding).…”
Section: The Clinical Effects Of the Different Conditions Is An Impormentioning
confidence: 99%
“…Among undergraduates at the University of Cambridge stress peaks during the exam term -two months of revision and examinations which determine the outcome of their entire academic year; grades can play a crucial role in defining their career paths. In 2015 the University of Cambridge funded the Mindful Student Study: a randomised, waiting-list controlled trial of an 8-week manualised mindfulness program adapted to students 42 . In this trial we showed that mindfulness training reduces psychological distress among university students, particularly during the exam revision period, improving resilience to stress.…”
mentioning
confidence: 99%
“…Participants randomised to the intervention attended a median of seven sessions (inter-quartile range 2-7) including one person who attended no sessions at all, and six students who attended all the sessions. Eighteen participants (67% of those randomised to the intervention) attended at least half of the mindfulness course sessions, our pre-specified "minimum dose" 42 also used in previous studies 43 , and shown to produce meaningful change 44 . Three participants provided reasons for abandoning their mindfulness course; these were schedule conflicts or being too busy.…”
mentioning
confidence: 99%
“…En las últimas dos décadas la investigación en MF indica hallazgos benéficos para la salud en diversos contextos y poblaciones. Sin embargo, muchos científicos indican que a pesar de su popularidad y supuestos beneficios para la salud y el bienestar psicológico, aún faltan datos duros sobre la eficacia del MF en la clínica (Barnes, Hattan, Black & Schuman, 2017;Cho, Ryu, Noh & Lee, 2016;Goldberg,Tucker, Greene, Simpson, Kearney & Davidson, 2017;en el trabajo (D´Abundo, Cara & Kelly, 2016;Goyal, Singh & Sibinga, 2014;De Vibe, Solhaug, Tyssen, Friborg, Rosenvinge & Sørlie, 2013), y la escuela (Miller, Borsatto & Al-Salom, 2018;Dvořáková et al, 2017;Galante, et al, 2016). Una revisión de la literatura (Goldberg, Tucker, Greene, Simpson, Kearney & Davidson, 2017), encontró que solo el 10% de las investigaciones basadas en el MF utilizaron un grupo de control, y que por lo tanto no había forma de contrastar los hallazgos; varios estudios de meta-análisis han obtenido resultados modestos sobre la efectividad del MF en la reducción del estrés, ansiedad, depresión, dolor e ira en poblaciones clínicas y normales, así como en el incremento de la atención y productividad laboral y rendimiento escolar.…”
Section: Discussionunclassified
“…Algunos alumnos fueron capaces de afrontar los problemas, mientras que otros les costó comprender los objetivos del programa. Galante et al (2016), aplicaron el MF a 550 universitarios para reducir el distrés durante el período de exámenes, incrementar la resiliencia, y mejorar el desempeño académico de los estudiantes. Obtuvieron que el MF si produjo los resultados esperados en contextos reales, pero no en circunstancias ideales.…”
Section: Evidencias Que Cuestionan La Efectividad Del Mindfulnessunclassified